Herbicides and plant physiology. - Cobb, Andrew H., 1949- (Wiley-Blackwell, 2021)
"This Third Edition aims to update the reader on how herbicides contribute to modern agriculture, how they are discovered and developed, and interact with plant growth and development, and the environment. Since the publication of the Second Edition in 2010 there have been many advances in our understanding of plant physiology, especially regarding how plants function in tune with their ever-changing environment and how post-translational modifications provide regulatory control of most plant processes. Modern agriculture, however, still faces many challenges. The starting point of this book is weed biology. Subsequent chapters consider the modern plant protection products industry, how herbicides are discovered and developed, how they gain entry into the plant and move to their sites of action, and the basis of herbicide selectivity. Detailed and updated accounts follow of how herbicides interact with the major physiological processes in plants, leading to weed control. This begins with the inhibition of photosynthesis; followed by pigment biosynthesis; interactions with the plant growth regulator, auxin; lipid biosynthesis; amino acid biosynthesis; cell division; cellulose biosynthesis; the plant kinome; herbicide resistance; the development of genetically-modified-herbicide resistant crops and a consideration of some new targets for the future development of new herbicides"--